Unitarity constraints on ALP interactions - Brivio, Ilaria; Éboli, Oscar J. P.; Garcia, Maria Concepcion (Physical review, 2021)
We derive partial-wave unitarity constraints on gauge-invariant interactions of an axionlike particle up to dimension-6 from all allowed 2→2 scattering processes in the limit of large center-of-mass energy. We find that the strongest bounds stem from scattering amplitudes with one external axionlike particle and only apply to the coupling to a pair of SU(2)L gauge bosons. Couplings to U(1)Y and SU(3)C gauge bosons and to fermions are more loosely constrained.
Gesehen am 05.11.2021